The sacralisation of popular culture as adolescent lived spirituality - Apostolides, Anastasia (Stellenbosch Theological Journal, 2017)
Many adolescents are drawn to the fantasy, science fiction and urban fantasy genres (movies and books), genres whose main characters include witches, wizards, vampires, ghosts, angels, demons, aliens and various other supernatural beings and events. Books and movies such as The Hobbit, Lord of the Rings (film series), Harry Potter (film series), X-Files, Twilight (film series), Star Wars (film series), and so on, are not only fervently consumed by some adolescents but have also, in some instances, been sacralised by adolescents (see Hopper 2005:116, McAvan 2012:5–10, Kirby 2013:2). In this article it will be argued that the reason for this, is that adolescents while questioning their identities and exploring their spiritualties, need a ‘safe spiritual space’ for this journey, one which may be related as something akin to what Berger termed the ‘sacred canopy’ where order can keep chaos at bay (Berger 1967: 51). This article will build on a lived theology perspective of how the divine can be experienced in the sources offered by popular culture texts that may become a ‘sacred canopy’ under which the adolescents can express their spiritual journeys. This article hopes to contribute to the facilitation of more conversations taking place amongst parents, pastors and teachers on the importance of allowing adolescents more freedom in what movies and books they are allowed to see and read. These conversations may also be employed by pastors, parents and teachers as conversation openers with adolescents who are often reluctant to open up about topics that they find difficult to discuss. Osmer and Salazar-Newton (2014:70) encourage the church to ‘think of ways it can take advantage of the interest of children and youth in fantasy literature,’ on their spiritual life journeys.